An Endless Piece of Bread: Cesar Vallejo’s poetry - Lespada, Gustavo (Espergesia, 2016)
The present study focuses on César Vallejo’s latest poetic production, especially on rhythmical resources and linguistic disruptions as well as on the frank challenge to the canon of his time. Neologisms, Quechua terms, orthographic and lexical transgressions of all kinds, archaisms, irruptions of colloquial registers, and so on. They are all poetic resources decidedly politically oriented, i.e. they respond to a language policy. The intercalation of popular lan-guage in the midst of complex and subtle figurative procedures is an operation by which the voice of the common man is rescued and dignified. From the analysis of emblematic poems from Poemas humanos (Human poems) and España, aparta de mi este cáliz (Spain, take this chalice away from me), we shall be able to corroborate how in this period the convergence of the greatest social commitment (on the thematic level), with the formal audacity that already characterized Trilce, becomes evident.